THE EFFECT OF ORGANIC-Cr DIETARY SUPPLEMENTATION ON STRESS RESPONSE IN TRANSPORT-STRESSED BEEF CATTLE - Tanuwiria, U.H.; Santosa, U.; Yulianti, A.; Suryadi, U. (Diponegoro University, 2011)
Transportation over long distances resulted in stress at animal. Under these circumstances, animalusually manifest depression and the impact on physiological condition changes and loss of body weight.The objectives of the research were to examine effect supplementation of organic-Cr type into diets intransport-stress beef cattle on physiological condition, haematochemical (included were haematologicalcondition and blood chemical) and body weight changes. The experiment was conducted using 16 beefcattle those were transported by truck for a distance of 400 km from Malangbong to Tangerang. Theexperiment was arranged by Completely Randomized Design with four treatments and four replications.The dietary treatments consisted of R0 (basal diet without Cr supplemented), R1 (R0+3ppm organic-Crresulted of alkali hydrolysis), R2 (R0+3 ppm organic-Cr resulted from bioprocess), R3 (R0+3 ppmorganic-Cr resulted from bioremediation). The result indicated that type of organic-Cr supplementationat 3 ppm in diet did not influence physiological condition, haematochemical and body weight at beefcattle transported for seven hours. There was indication that beef cattle fed on control diet (without Cr)showed a stress symptom, their loss of body weight were higher (5.41%) compared to beef given dietcontains organic-Cr (3.72%, 5.04% and 4.83%, respectively for R1, R2 and R3).